Effect of gamma irradiation on GaN lateral Schottky barrier diodes. Issue 1 (1st November 2022) - Duan, Chao; Wu, Zhaoxi; Meng, Meng; Zhao, Shenglei; Wang, Xu; Yu, Qingkui
Abstract : The effect of gamma irradiation on GaN lateral Schottky barrier diodes (SBDs) has been investigated. Six gamma irradiation conditions were carried out, namely 100/500 k rad, 1 M rad, 100/500 k rad and 100°C, and 1 M rad and 100°C. All the irradiated devices have a similar parameter variation tendency. There is no change for turn-on voltage. The on-state resistance is reduced from 5.32 5.53 Ω to 5.10 5.26 Ω, while the reverse leakage at -100 V is increased from 3.53 4.99 μA to 4.13 5.79 μA. The interface information extracted is improved slightly, demonstrating the anode/GaN interface is improved, and the passivation/AlGaN interface may be degraded. The slight variation of irradiated performance demonstrates that the GaN lateral SBDs are hardly affected by gamma irradiation.